Bag moths (Psychidae, Lepidoptera) of the Łódź Upland - Marciniak, Barbara (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2002)
Results of the investigations of Psychidae (Lepidoptera) of the Łódź Upland were presented. In total 15 species (41.7% of fauna of our country) were found. Their distribution was analysed.